Exposure-response relationship of ramucirumab in patients with advanced second-line colorectal cancer: exploratory analysis of the RAISE trial - Cohn, Allen Lee; Yoshino, Takayuki; Heinemann, Volker; Obermannova, Radka; Bodoky, György; Prausová, Jana; Garcia-Carbonero, Rocio; Ciuleanu, Tudor; Garcia-Alfonso, Pilar; Portnoy, David C; Van Cutsem, Eric; Yamazaki, Kentaro; et al. (Cancer chemotherapy and pharmacology, 2017)
PURPOSE: To characterize ramucirumab exposure-response relationships for efficacy and safety in patients with metastatic colorectal cancer (mCRC) using data from the RAISE study. METHODS: Sparse pharmacokinetic samples were collected; a population pharmacokinetic analysis was conducted. Univariate and multivariate Cox proportional hazards models analyzed the relationship between predicted ramucirumab minimum trough concentration at steady state (C min,ss) and survival. Kaplan-Meier analysis was used to evaluate survival from patients in the ramucirumab plus folinic acid, 5-fluorouracil, and irinotecan (FOLFIRI) treatment arm stratified by C min,ss quartiles (Q). An ordered categorical model analyzed the relationship between C min,ss and safety outcomes. RESULTS: Pharmacokinetic samples from 906 patients were included in exposure-efficacy analyses; samples from 905 patients were included in exposure-safety analyses. A significant association was identified between C min,ss and overall survival (OS) and progression-free survival (PFS) (p < 0.0001 for both). This association remained significant after adjusting for baseline factors associated with OS or PFS (p < 0.0001 for both). Median OS was 11.5, 12.9, 16.4, and 16.7, and 12.4 months for ramucirumab C min,ss Q1, Q2, Q3, Q4, and placebo group, respectively. Median PFS was 5.4, 4.6, 6.8, 8.5, and 5.2 months for ramucirumab C min,ss Q1, Q2, Q3, Q4, and placebo group, respectively. The risk of Grade ≥3 neutropenia was associated with an increase in ramucirumab exposure. CONCLUSIONS: Exploratory exposure-response analyses suggested a positive relationship between efficacy and ramucirumab exposure with manageable toxicities in patients from the RAISE study with mCRC over the ranges of exposures achieved by a dose of 8 mg/kg every 2 weeks in combination with FOLFIRI.
Keywords: senioři; kolorektální nádory; Ramucirumab; monoklonální protilátky; ramucirumab; Colorectal Neoplasms; mužské pohlaví; Antibodies, Monoclonal; Antineoplastic Agents; FOLFIRI; Colorectal cancer; Disease-Free Survival; ženské pohlaví; protinádorové látky; Humans; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; Female; Aged; přežití bez známek nemoci; lidé; Male; Second line; Exposure–response